Neuroprotective Effect of Ginseng Fibrous Root Enzymatic Hydrolysate against Oxidative Stress - Yuhua Zhu; Ziyan Wang; Shuxuan Yu; Chong Zhao; Baofeng Xu; Rui Liu; Li Xu; Yi Guo (Molecules, 2022)
Oxidative stress is one of the potential causes of nervous system disease. Ginseng extract possesses excellent antioxidant activity; however, little research on the function of the ginseng fibrous root. This study aimed to investigate the neuroprotective effects of ginseng fibrous root to alleviate the pathogenesis of Alzheimer’s disease (AD) against oxidative stress. Ginseng fibrous root enzymatic hydrolysate (GFREH) was first prepared by digesting ginseng fibrous roots with alkaline protease. In vitro, the GFREH showed antioxidant activities in free radical scavenging mechanisms. With a cellular model of AD, GFREH inhibited the increase in Ca2+ levels and intracellular ROS content, maintained the balance of mitochondrial membrane potential, and relieved L-glutamic acid-induced neurotoxicity. In vivo, GFREH improved the survival rate of Caenorhabditis elegans (C. elegans) under oxidative stress, upregulated SOD-3 expression, and reduced reactive oxygen species (ROS) content. Therefore, our findings provide evidence for the alleviation effect of GFREH against oxidative stress in neuroprotection, which may accelerate the development of anti-Alzheimer’s drugs and treatments in the future.